2017
DOI: 10.1007/s00787-017-1040-9
|View full text |Cite
|
Sign up to set email alerts
|

Potential for diagnosis versus therapy monitoring of attention deficit hyperactivity disorder: a new epigenetic biomarker interacting with both genotype and auto-immunity

Abstract: In view of the need for easily accessible biomarkers, we evaluated in ADHD children the epigenetic status of the 5'-untranslated region (UTR) in the SLC6A3 gene, coding for human dopamine transporter (DAT). We analysed buccal swabs and sera from 30 children who met DSM-IV-TR criteria for ADHD, assigned to treatment according to severity. Methylation levels at six-selected CpG sites (among which, a CGGCGGCGG and a CGCG motif), alone or in combination with serum titers in auto-antibodies against dopamine transpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
67
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(71 citation statements)
references
References 83 publications
4
67
0
Order By: Relevance
“…They found that less methylation was associated with greater MPH response [12]. Another study detected negative association between DAT1 methylation and scores of hyperactivity [44].…”
Section: Discussionmentioning
confidence: 95%
“…They found that less methylation was associated with greater MPH response [12]. Another study detected negative association between DAT1 methylation and scores of hyperactivity [44].…”
Section: Discussionmentioning
confidence: 95%
“…4,10 Consequently, candidate studies have primarily focused on genes related to dopamine function. For instance, DNA methylation alterations in DRD4 [11][12][13] , DRD5 12 , and DAT1 12,14 genes have been associated with ADHD diagnoses or symptoms, though not consistently 15 . Beyond the candidate gene approach, three studies tested DNA methylation across the whole genome.…”
Section: Introductionmentioning
confidence: 99%
“…A longitudinal study has shown association between SP6 gene DNA methylation, amygdala/hippocampal volume ratio, and psychopathology, supporting the role of DNA methylation as a longitudinal epigenetic predictor. Moreover, blood methylation levels of 5‐HTT and/or BDNF genes have been suggested as promising biomarkers for prediction of pharmacological or psychotherapeutic treatment response in patients suffering from MDD, BD, BPD, PTSD, SCZ and ADHD . In addition to these genes, recent studies have reported a four‐locus model involving the CYP3A4 gene that significantly alters risperidone treatment response of SCZ patients .…”
Section: Potential Use Of Epigenetics For Mechanistic Insight and Novmentioning
confidence: 99%
“…Moreover, blood methylation levels of 5-HTT and/or BDNF genes have been suggested as promising biomarkers for prediction of pharmacological or psychotherapeutic treatment response in patients suffering from MDD, 69 BD, BPD, 70 PTSD, 71 SCZ 72 and ADHD. 73 In addition to these genes, recent studies have reported a four-locus model involving the CYP3A4 gene that significantly alters risperidone treatment response of SCZ patients. 74 Finally, the generation of a DNA methylation biosignature in blood or © 2018 The Authors Psychiatry and Clinical Neurosciences © 2018 Japanese Society of Psychiatry and Neurology saliva has been shown to improve a suicide-prediction model.…”
Section: Potential Use Of Epigenetic Modifications As Biomarkersmentioning
confidence: 99%